Repeatability and reproducibility of relative cerebral blood volume measurement of recurrent glioma in a multicentre trial setting - Smits, Marion; Bendszus, Martin; Wick, Wolfgang; Heiland, Sabine (European journal of cancer, 2019)
Measurement of relative cerebral blood volume (rCBV) with dynamic susceptibility contrast (DSC) magnetic resonance imaging (MRI) is used extensively f…
Gesehen am 04.09.2019